Management of advertising in the field of mass - A. Guseinova, Aigul (2018)
In the modern information society advertising activity has become an important element of the system of social and economic policy. Undoubtedly, if production of domestic products, works and services is advertised, we understand that the means from the sale of such goods are purposed to pay for compatriots, to increase the budgets of this state, and not to increase the incomes of foreigners. In the first approximation, the advertisement of domestic competitive goods in their country and abroad is a progressive matter. If foreign goods are advertised in our country on the condition that domestic goods production is provided with not less but slightly greater benefits than foreign goods, then fair and decent advertising of foreign goods can and should be considered fair under the conditions: Such advertising allows citizens to satisfy their needs in a more attractive foreign product, compensating for the loss of a certain number of jobs in a given country; Such advertising encourages domestic producers to improve the quality of their goods in order to "equitably" compete in "their" and "foreign" territory, etc.If, for example, conditions are created in our country that no domestic goods of even better quality can compete with foreign ones because of extremely high cost due to a specially created and unfair tax burden to domestic commodity production, such advertising with the cleared way is harmful. Its harmfulness is hidden in a special way for an inefficient taxation system, etc. Therefore, in this paper, the authors emphasize the need to conduct research on the content of advertising activities and its role in socio-economic policy.